Does nitrogen matter for legumes? Starter nitrogen effects on biological and economic benefits of cowpea (Vigna unguiculata L.) in Guinea and Sudan Savanna of west Africa - Nurudeen, A.R.; Larbi, Asamoah; Kotu, Bekele Hundie; Tetteh, F.M.; Hoeschle-Zeledon, I. (MDPI, 2018)
The hypothesis that application of starter nitrogen (N) fertilizer to cowpea may increase grain and fodder yields and profitability was tested in the Guinea and Sudan savanna zones of northern Ghana. Two cowpea varieties (Apagbaala: grain-type and Padi-Tuya: dual purpose) and three N fertilizer rates (0-30-30, 15-30-30 and 30-30-30 N-P2O5-K2O kg/ha) were evaluated using a 2 × 3 factorial treatments arrangement in a randomized complete block design with three replicates. Grain and fodder yields, 100 seed weight (SW) and net return of Padi-Tuya increased significantly compared with Apagbaala in both zones. Application of starter N fertilizer increased grain yield, fodder yield, N use efficiency (NUE) and net return by more than 30% compared with the control in both zones. Padi-Tuya cowpea with 15 kg/ha N fertilizer was risk efficient at all risk aversion levels when only grain was considered, but Padi-Tuya with 30 kg/ha N fertilizer becomes the most risk efficient option when the value of fodder was included. The results suggest that small-scale farmers could apply starter N fertilizer at either 15 kg/ha N for grain only or 30 kg/ha N for both grain and fodder yields improvement of cowpea in West Africa and similar ecologies.